Legal Aspects of the Supply Chain Cybersecurity in the Context of 5G Technology - Besiekierska, Agnieszka (Review of European and Comparative Law, 2022)
The 5G networks are considered to be crucial for the digital transformation of the economy and society and therefore will be subject to the regulations concerning the supply chain cybersecurity. Numerous European documents point out cyberthreats relating the supply chain and oblige the Member States to introduce laws enabling risks assessment of suppliers, which, in accordance with the EU Toolbox, should cover technical and non-technical factors such as dependence of the supplier from third countries. So far, Poland has not introduced regulations in this respect and provisions on recognition of high-risk suppliers to be implemented in the Act on national cybersecurity system are still in the draft phase. The key criterion for the risk assessment will be a threat to the national security, which is vague and may in the future be difficult for interpretation due to the specifics of the proceedings (limited right to participate in the proceedings, limited access to information). As the effects of the proceedings are far-reaching (the obligation to withdraw the products), they may potentially raise some concerns with regard to the freedom of economic activity. The new cutting-edge technologies such as 5G, as well as the need to ensure cybersecurity along with the on-going political polarization in the world will increase the amount of legal regulations relating to the supply chain cybersecurity.